Digital transformation of physical education: the experience of creating an environment in the system of training specialists in physical education and sports - Petrov P.K.; Dmitriev O.B.; Akhmedzyanov E.R. (Theory and Practice of Physical Culture, 2025)
The purpose of the study is to generalize the experience of forming a digital educational environment for training specialists in physical culture and sports in the context of digital transformation of education on the example of Udmurt State University. Methodology and organization of research. The following methods were used to prepare the article: analysis and generalization of scientific and methodological literature on issues related to the digital transformation of education in general and physical culture education in particular, a retrospective analysis of the formation and formation of the digital educational environment in the system of training specialists in physical culture and sports based on the authors’ experience. Research results and conclusions. The article reveals the features of the formation of the digital educational environment in the context of the digital transformation of physical culture education, the problems associated with the digital transformation of physical culture education and the formation of the digital educational environment, taking into account the transition to a new system of higher education, the development of new sports, the features of the training direction “Physical Culture”, oriented to practice-oriented, the need for both students and teachers to develop digital competencies necessary for training personnel for the digital economy. The analysis of the obtained results will make it possible to purposefully improve the digital educational environment in the system of training specialists in physical culture and sports in the areas of organizing the educational process, scientific activities, educational work, in the direction of administrative management and strengthening the material and technical base of the university, taking into account the development of modern digital technologies.